REVIEW ON BELL'S PALSY - P, Kuzhalvaimoazhi; Thenmozhi; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Bell's palsy is an acute idiopathic peripheral nerve palsy that affects the seventh cranial nerve, the facial nerve, which supplies all the muscles of facial expression. The seventh cranial nerve carries predominantly motor fibers but also supplies some autonomic innervation, sensation to the top part of the ear, and taste to the anterior two thirds of the tongue. It is responsible for lacrimation, tearing. But pathogenesis remains controversial. The paralysis causes disturbances among patients not only in social activities, lifestyle, and psychological aspects but also in functional activities, like the ability to eat, drink, and speak. Many options of treatment exist, including medications in the form of steroids, antivirals, and neural multivitamins; surgery; and also physiotherapy.